Brother's keeper - Compton, Ralph (Penguin Books, 2015)
The life of a cowboy suits Thalis Christie just fine. A puncher for the Crescent H in Texas, he loves what he does and is damn good at it too. He doesn't even mind being away from his family--he's got good friends to keep him from getting too homesick. That is, until his folks write, imploring him to hunt down his brother, Myles, who's been shot while prospecting in the Black Hills. Thalis sets out to do his family duty and find his little brother--still alive, he hopes. Thalis has got his partner, Ned Leslie, by his side, as well as some other surprising travel companions, including the famous Wild Bill Hickok. But as he follows his brother's wandering trail across the country, leading him to encounter deadly obstacles from Texas to Blood Gulch, he begins to wonder if he can ever return to the comfortable life he used to lead--or if he even wants to.